DESIGN OF E-PAYMENT USING RFID (RADIO FREQUENCY IDENTIFICATION) BASED ON WEBSITE ( CASE STUDY: BTH RESTO) - Dina Nurfaujiah Apipah Firdaus; Agus, Agus Ramdhani Nugraha (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
The use of technology in payment systems has influenced changes in payment patterns. BTH Resto, as one of the canteens in the BTH Tasikmalaya University environment, experiences challenges in managing electronic payments because it does not yet have a special E-payment for the Resto. This study aims to develop E-payment using RFID (Radio Frequency Identification) based on the website at BTH Resto to improve efficiency and practicality. Electronic payment design using USB RFID Reader technology consists of several stages starting from the problem analysis stage, system design, Flowchart and system implementation. The digital payment system using RFID is able to overcome the increasing demand for digital payments, as well as separate the restaurant transaction history from employee personal data. Based on the tests conducted, the results obtained that the USB RFID Reader can be used as an electronic payment tool. With the adoption of this technology, the speed of service, reducing queues, and updating the payment system.